Language attitudes towards dialects of Arabic in Egypt - Eltouhamy, Ibrahim (AUC Knowledge Fountain, 2015)
It has been widely believed that a negative attitude is consistently to be found with the rural dialects of Egyptian Arabic, and that their speakers, especially those who emigrate to urban areas, ultimately tend to change their dialects to adapt, at least partially, to the prestige variety of vernacular Arabic, in this case the urban Cairene dialect (Bassiouney, 2009; Haeri, 1991; Miller, 2005; Woidich, 1994). In this regard, language attitudes towards rural dialects of Arabic in Egypt have been only slightly investigated sociolinguistically, as the majority of studies of Arabic language attitudes have been limited to investigating speakers’ attitudes toward MSA and the dialects of the main cities. The purpose of this study is to investigate language attitudes towards two rural dialects in Egypt; fallaHi and Saiidi, in comparison with attitudes towards the urban Cairene dialect. The study utilizes the verbal guise technique of the indirect approach to research language attitude. A comparison was made between the three dialect groups on eight traits: smartness, kindness, deception, religiousness, leadership, arrogance, preferability to work with and preferability to get married to. 155 participants have taken part in an online questionnaire, placing their evaluative reactions to 12 speakers - two males and two females from each dialect group - on a Likert scale. Both descriptive and inferential statistics were applied to the data, trying to generate answers to the attitude question of the study, and to the investigation the effect of gender of the listeners. Participants’ correct identification of the three dialects were measured as well. The findings suggest that attitudes towards the three dialects of Arabic in Egypt vary according to the personality characteristics of the speakers and it also varies according to the gender of the listeners. In general, raters hold positive attitudes towards the urban dialect of Cairo as far as power traits are concerned. On the other hand, rural dialects of fallaHi and Saiidi elect positive attitudes when solidarity traits are concerned. It has been also found that male raters are more tolerant towards speakers of rural dialects than female raters. For females, the dialect of the speakers approves to be a matter of significance, as it appears in the results. Raters was found to be more familiar with the Cairene dialect than with the fallaHi and Saiidi dialects. They were able to correctly identify the Cairene dialect with a higher percentage. Male raters were better than females in recognizing the dialects correctly.